Skin Reactions and Quality of Life after X-Ray Therapy of Basal Cell Carcinoma - Jette Skiveren; Maria Rudkjaer Mikkelsen; Helle Daugbjerg; Hans Christian Wulf (Journal of Skin Cancer)
Background. Advanced basal cell carcinoma (BCC) is often treated by surgery or X-ray therapy. The consequences of X-ray therapy on the patients’ health-related quality-of-life (HRQOL) have so far not been described. Objectives. To quantify quality of life in BCC patients before and after X-ray therapy compared with matched healthy controls. Materials. Twenty-five patients (mean age 69) with BCC completed the Dermatology Life Quality Index (DLQI) before and two weeks and three months after X-ray therapy and their results were compared with the DLQI scores for 25 matched controls. Results. Compared to the healthy controls the patients' DLQI score was significantly higher before and 2 weeks after X-ray therapy (P=0.005; P=0.000). The patients' DLQI score decreased significantly from baseline to three months after X-ray therapy (P=0.024), when it became similar to that of the healthy controls (P=0.819). Three months after X-ray therapy eight patients had no skin reactions, 11 had slight atrophy, pigmentation change, and/or some hair loss, four had patch atrophy, moderate telangiectasia, and/or total hair loss. Conclusions. BCC has a negative effect on patients' quality of life. The study shows that HRQOL normalises shortly after X-ray therapy, despite minor skin manifestations.